Natural Convection in an Inclined Square Enclosure Containing Internal Energy Sources - Islam, Md. Tofiqul; Saha, Sumon; Mamun, Md. Arif Hasan; Saha, Goutam (Journal of Mechanical Engineering, 2008)
Natural convection in an inclined differentially heated square enclosure containing internally heated fluid has been investigated numerically using the Galerkin finite element method. The horizontal walls are adiabatic, while the side walls are isothermal but kept at different temperatures. Flow and heat transfer characteristics through isotherms, streamlines and average Nusselt numbers have been presented for the external Rayleigh number 103 to 106, internal Rayleigh number 105 to 108 and inclination angles 0Â° to 30Â°. The obtained computational results indicate that the strength of the convective currents depends on the internal energy. Heat removal rate is optimized at zero inclination angle for relatively weak external heating mode for all values of internal energy. Keywords: Natural convection, finite element method, square enclosure, Rayleigh number. doi:10.3329/jme.v37i0.816 Journal of Mechanical Engineering Vol.37 June 2007, pp.24-32